PENGARUH IKLIM ORGANISASI TERHADAP HUBUNGAN INTERPERSONAL: STUDI KASUS BADAN EKSEKUTIF MAHASISWA 17 AGUSTUS 1945 SURABAYA - Meilina, Meilina; Sumarah, Noorshanti; Soenarjanto, Bagus (Universitas 17 Agustus 1945 Surabaya, 2015)
This research is motivated by the growing climate in an organization and interpersonal relationshipsbetween members of an organization that is bound to happen because the real man is virtually impossibleto live without communicating. In an organization there are goals of the organization in which themembers of the organizational duties. Surely spada any organization that is therein AKN climate differentfrom the climate in other organizations. August 17, 1945 Surabaya University has six faculty that each -each have the Mahasiswa.Hal Executive Board encourages the writer to determine whether there was aneffect of organizational climate on the interpersonal relationships of its members. The influence willaffect not or achievement of the organization itself. The method used in this study is a survey method is amethod of research using a questionnaire as a data collection instrument. While this kind of research is aquantitative correlational research. This study uses a statistical formula product moment using dataprocessing SPSS 22 for windows conclusion that organizational climate (X) which includes indicatorsSense of Responsibility, Standard or expectations about quality, reward or reward, Sense of fraternityand team spirit is weak effect on interpersonal relationships (Y ) which includes indicators of thecharacteristics of individuals involved, the group properties, environmental properties Student ExecutiveBoard UNTAG Surabaya worth of 2.54 which means that the level of influence is weak.Keywords: effect, organizational climate, interpersonal relations.